Results of Renogram and eGFRin Assessing Kidney Function of Chronic Kidney Disease Patients (Medico Legal Update, 2021)
Background: The ability to assess kidney function properly has important health implications. Glomerularfiltration rate (GFR) is still accepted as the best measurement index of kidney function. The formula of theModified of Diet in Renal Disease (MDRD) is currently widely used by the medical community to estimateGFR (estimated GFR or eGFR). The renogram with radiofarmaka I131-Hippuran is considered to have aninherent accuracy of inulin cliren as the gold standard of GFR measurement.Objective: To determine the description of renogram and eGFR’s results in assessing kidney function ofCKD patients.Method: This study was a retrospective observational that used medical records from 113 CKD patientsundergone renogram examination at Dr. Soetomo General Hospital Surabaya in 2012. eGFR was calculatedbased on the serum creatinine, age, and sex of the patient. Data of renogram and eGFR examination werepresented descriptively.Results: We obtained male of 63% and female of 37% with age range between 20-69 years. The highestpercentage in the age range of 50-59 years. The CKD cases in this study were mostly caused by urinary tractstones of 44%. The most common renogram results were 2 kidney failure by 48% and the highest eGFR was